SOME ASPECTS OF THE MEDIO-ACTIVE VERBS IN THE MEGRELIAN AND LAZ LANGUAGES - Akhalaia, Nato (Online Journal of Humanities ETAGTSU, 2016)
Since Dionysius THE Thrax singled out the category of the Medial Voice, its formulation has not under gone any significant changes: when one (active) verb form expresses an action and another one (passive) denotes a feeling, thereis amedium form between them, which, according to its outward signs belongs to the first category whereas according to its meaningto the other ones:such forms are referred to as Medial Voice forms. Medial voice forms are unmarked members of the opposition. They do notpossess adistinct shape, and resemble Active Voice in terms of its form on the one hand and Passive Voice in terms of its function, on the other. However, in this respect theydiffer bothfrom the first voice(according to the function) and from the second one (according to the form). In terms of similarities and differences Medial voice forms occupythe middle position between Active and Passive voices. That’s why we refer to them as "Medial" forms. This article briefly examines Medial verbs and particularly, the characteristic features of Medio-Actives in the Megrelian and Laz Languages based on relevant examples. It is noted that due to the verbs’ formal and semanticdifference these types of verbs in the Megrelian and Laz Languages are known for their diversity and complexity. This article discusses dynamic and static issues regarding the voice. More specifically, Medio active verbforms are examined within the context of static verbs. In addition, this article also analyses the issues connected with the category of aspect and prefixes. Full Text (PDF)